-1(3x+4)-4x=-2(4x-3)+2

Simple and best practice solution for -1(3x+4)-4x=-2(4x-3)+2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -1(3x+4)-4x=-2(4x-3)+2 equation:


Simplifying
-1(3x + 4) + -4x = -2(4x + -3) + 2

Reorder the terms:
-1(4 + 3x) + -4x = -2(4x + -3) + 2
(4 * -1 + 3x * -1) + -4x = -2(4x + -3) + 2
(-4 + -3x) + -4x = -2(4x + -3) + 2

Combine like terms: -3x + -4x = -7x
-4 + -7x = -2(4x + -3) + 2

Reorder the terms:
-4 + -7x = -2(-3 + 4x) + 2
-4 + -7x = (-3 * -2 + 4x * -2) + 2
-4 + -7x = (6 + -8x) + 2

Reorder the terms:
-4 + -7x = 6 + 2 + -8x

Combine like terms: 6 + 2 = 8
-4 + -7x = 8 + -8x

Solving
-4 + -7x = 8 + -8x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '8x' to each side of the equation.
-4 + -7x + 8x = 8 + -8x + 8x

Combine like terms: -7x + 8x = 1x
-4 + 1x = 8 + -8x + 8x

Combine like terms: -8x + 8x = 0
-4 + 1x = 8 + 0
-4 + 1x = 8

Add '4' to each side of the equation.
-4 + 4 + 1x = 8 + 4

Combine like terms: -4 + 4 = 0
0 + 1x = 8 + 4
1x = 8 + 4

Combine like terms: 8 + 4 = 12
1x = 12

Divide each side by '1'.
x = 12

Simplifying
x = 12

See similar equations:

| 5x=(400/4) | | 2x+x-3+x=22 | | y=x^2-8x+k | | 2x^8-4x^7+10x^6=0 | | x/48=6/12 | | 3x+3(x+2)=6 | | 2x=(400/4) | | 14-3y=-7 | | -3k-39=-5(8k-7) | | -6(1+7a)=27 | | 4t(5t-4t)=0 | | 5/2x=0 | | 65ab^3-45a^2b^2=0 | | 16=9x+2-2x | | 5.4x=7.02 | | 5n^2-16n=-3 | | 7x-8=x+7 | | 0.15(x+10)=8x+20 | | 5-2a=5a-2 | | -1(3x+4)-4r=-2(4r-3)+2 | | 2x+5=6x-9 | | x+-2x+4=3 | | 16+5a=56 | | x^2+4x+4y^2=0 | | 6x+14=5x+12 | | 3(m^2+10m+23)=0 | | r^2+3r=10 | | 7a-7+6a=10-4a | | 3x^2+11x-1-x^3=0 | | y=-2(x+3)2+2 | | x/2=20/10 | | 10t+3(1-4t)= |

Equations solver categories